Dietitians' experiences and perspectives regarding access to and delivery of dietetic services for people with type 2 diabetes mellitus. Issue 2 (February 2020) - Siopis, George; Colagiuri, Stephen; Allman-Farinelli, Margaret
Abstract: Aims: Dietetic intervention improves glycaemic control of type 2 diabetes mellitus (T2DM). The aim of this study was to explore the views of Australian dietitians with respect to the nutritional management of people with T2DM, patient access to dietitians and any suggested improvements for access to and delivery of dietetic services. Methods: Semi-structured interviews were conducted via telephone with 31 dietitians counselling people with T2DM and consulting a minimum of two sessions per week in private and/or non-private practice. Results: Participants came from urban and rural areas, public and private practice and with a range of years of practice. Themes that emerged from the interviews included the importance of dietetic services for people with T2DM ; the referral pathways and beliefs about lack of referrals to dietitians ; the perceptions on adequacy of the current dietetic services available for people with T2DM ; and the recommendations on services available for people with T2DM . Conclusion: Considering the evidence that diet is key in the prevention and management of T2DM, it is suggested current funding and service provision be reviewed with a focus on treating the aetiology of diabetes. Abstract : Diet; Health sciences; Public health; Clinical research; Health profession; Type 2 diabetes mellitus; Diabetes; Diet; Dietitian; Qualitative research; Health services